Endothelial PDGF-CC regulates angiogenesis-dependent thermogenesis in beige fat - Takahiro Seki (Nature Portfolio, 2016)
Cold-induced activation of thermogenesis in white adipose tissue (WAT), or ‘beiging’, is associated with WAT angiogenesis. Here the authors show that PDGF-CC is secreted from endothelial cells in the context of WAT angiogenesis and its paracrine action on adipocytes contributes to cold-induced beiging.